2011
DOI: 10.1161/circgenetics.110.957688
|View full text |Cite
|
Sign up to set email alerts
|

Familial History of Stroke Is Associated With Acute Coronary Syndromes in Women

Abstract: Background-Stroke in female first-degree relatives (FDRs) is a powerful risk factor for ischemic stroke in women, but its association with acute coronary syndromes (ACS) is unknown. Family history (FH) of stroke is omitted from existing myocardial infarction risk prediction tools, which perform less well in women than in men. Our objective was to study the sex-of-parent and sex-of-proband interactions for FH of stroke in ACS patients. Methods and Results-In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…25,26 Existing research is however based on the associated risk in populations with a higher mean age and thus older parents, and our population might be too young to demonstrate any such association.…”
Section: Discussionmentioning
confidence: 87%
“…25,26 Existing research is however based on the associated risk in populations with a higher mean age and thus older parents, and our population might be too young to demonstrate any such association.…”
Section: Discussionmentioning
confidence: 87%
“…4, 5 Twin and family studies have demonstrated that both IS and CAD are highly heritable 6, 7 with some evidence of a shared heritability for both diseases. 8 …”
Section: Introductionmentioning
confidence: 99%
“…3 These data also indicate that stroke and coronary artery disease share genetic factors, as a family history of coronary artery disease is associated with an increased risk of large-artery stroke, 5 and a family history of stroke is associated with acute coronary syndrome. 6 Furthermore, a family history of stroke is also strongly associated with risk factors for stroke, such as hypertension and diabetes mellitus, which makes it important to determine whether any identified genetic factors predispose patients to stroke indirectly via risk factors, or independently of the risk factors. 7 Sex differences have also been reported: women were found to be approximately 50% more likely to have a maternal history of stroke than a paternal history of stroke, whereas no similar excess exists in men.…”
Section: Introductionmentioning
confidence: 99%